Robotics in General Surgery - Kim, Keith Chae (Springer New York : Imprint: Springer, 2014)
Robotics in General Surgery provides a comprehensive review of the current applications of the robotic platform in all the general surgery subspecialties. Additionally, for each subspecialty it serves as a procedure-oriented instruction manual in terms of technical details of procedures, including fundamentals of robot positioning and trocar placement, step-by-step description of procedures, comprehensive discussions of advantages, limitations, indications, and relative contraindications of using the robotic approach.  The text also discusses the challenges and steps to overcoming these challenges in transitioning from a minimally invasive to a robotic practice/surgeon.  Lastly, this volume addresses emerging technology in robotics and the impact that the robotics platform will have on not only practice of surgery, but also in the education of surgeons at all levels. Written by experts in the field of robotic surgery, Robotics in General Surgery is a valuable resource for general surgeons of all levels including residents, fellows and surgeons already in practice.